일부지역 유아교육관련 학과 학생의 구강보건교육 효과 - 구효진(Hyo-Jin Goo) (한국구강보건과학회지, 2020)
Objectives: The purpose of this study is to evaluate the effects of oral health education for students in departments related to early childhood education. Methods: This study was conducted in September 2018 with 40 students enrolled in the Department of Infants and Toddlers at Masan University. After explaining the purpose of the study, the students who consented were surveyed through a self-written questionnaire before and after oral health education. Statistical analysis of collected data was done using SPSS 20.0 program. The general characteristics of the subjects were analyzed by technical statistics. The changes before and after oral health education were analyzed by paired t-test. The help of oral health education according to oral health education was analyzed by chi-square test. The significance level for significance determination was 0.05. Results: It was found that there were 15% of oral health education experiences related to infants, 85.0% of non-existent oral health education experiences, and 47.5% of non-oral health education experiences related to general education. After oral health education, the importance of oral health among the changes in oral health awareness showed the highest increase rate(p<0.05). Among oral health knowledge, tooth-related knowledge showed the highest increase rate(p<0.05). The correct answer rate of behavioral knowledge required for oral health care and instruction in infants showed the highest increase rate from 67.4% before training to 93.0% after training during the brushing period(p<0.05). After oral health education for infants, the brushing time of infants was the highest with 30.3%(p<0.05). Expectations for the right brushing method were highest. After oral health education, the most increased level of help was fluoride coating and sealant(p<0.05). Conclusions: For proper oral health management of preschool children, systematic oral health education should be provided to early childhood education and students. KCI Citation Count: 0